Effectiveness of KS elements in satellite orbit prediction using earth’s gravity, drag and solar radiation pressure - R. Saritha Kumari, T.; Xavier James Raj, M. (International Journal of Advanced Astronomy, 2020)
Satellite moving under the gravitational field of Earth deviates from its two-body elliptic orbit, due to the combined effects of the gravitational field of Earth, atmospheric drag, solar radiation pressure, third-body gravitational effects, etc. This paper utilizes the KS regular element equations to solve Newtonian equations of motion to obtain numerical solution with respect to perturbing forces, like, Earth's gravity (includes zonal, sectorial and tesseral harmonics terms), atmospheric drag and solar radiation pressure. Effectiveness of the theory is illustrated by comparing the results with some of the existing theories in literature.Â